If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + bx = 7 Reorder the terms: bx + 5x = 7 Solving bx + 5x = 7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5x' to each side of the equation. bx + 5x + -5x = 7 + -5x Combine like terms: 5x + -5x = 0 bx + 0 = 7 + -5x bx = 7 + -5x Divide each side by 'x'. b = 7x-1 + -5 Simplifying b = 7x-1 + -5 Reorder the terms: b = -5 + 7x-1
| 3(1+5x)-1=-103 | | -8.6q+13.32=-18.4q+6.04+9.1q | | 5x+6x+7=5x-7 | | 4x-2=13x+16 | | 2(15r+10)=-80 | | 17f+8=18f-6 | | 7w-w=6w | | (14x)Y-7=(7x)Y+7 | | 10b-8=10b+7 | | 2(x+3)x=5 | | -1xy=10+2y | | -7-4f=-4f-1 | | 100+y=23 | | 5y+4y-12=0 | | y=-0.3x^2+2.4x+4 | | x^2y-16y^3=0 | | x+-7=10 | | v=35v-16 | | 0=r-r | | 12x+12=11x-44 | | -12(x-0.5)+3=-6x+75 | | 6(4+5)=2f-8 | | 10h=-1+10h | | z=15+2(x+y)findx | | 17x^3+34x^2-85x-102=0 | | -6+8v=5v | | f(x)=7Ln(3x+2) | | -6+8=5v | | 3x+9+18x+3=264 | | t*2=2 | | youre=dung | | q=10q-9q |